Identification of species of the Euterpe genus by rare earth elements using inductively coupled plasma mass spectrometry and linear discriminant analysis - Santos, Vivian Silva; Nardini, Viviani; Cunha, Luis Carlos; Barbosa, Fernando; De Almeida Teixeira, Gustavo Henrique [UNESP] (Elsevier B.V., 2014)
The acai (Euterpe oleracea Mart.) and jucara (Euterpe edulis Mart.) produce similar fruits which are rich in energy, minerals, vitamins and natural compounds with antioxidant and anti-inflammatory properties. Although the drink obtained from these species is similar, it is important to develop tools to establish the identity of the fruit species and growing regions. To assess claims of origin and for other purposes, we use multivariate analysis to investigate the differentiation of acai and jucara fruits based on rare earth element (REE) content determined by Inductively Coupled Plasma Mass Spectrometry. REE content, in particular Sm, Th, La, Pr, Gd, and especially Ce and Nd varied between species. PCA analysis was not efficient in differentiating acal from jucara fruit samples. In contrast, LDA analysis permitted a correct differentiation between species with a predictive ability of 83.3%. The methodology that we have applied confirms that REE can be used to differentiate between acal and jucara fruit samples and to identify their origin. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Euterpe edulis Mart; Euterpe oleracea Mart; ICP-MS; LDA; PCA; Multivariate analysis